Density or variability: is it time for a paradigm shift in ecology? - Uchmanski, Janusz (Ecological Questions, 2022)
In ecology, the paradigm of density is commonly used. It is used to construct mathematical models and to plan and interpret ecological experiments. This leads to mathematical models using differential equations in ecology. It seems, however, due the fundamental discontinuity in ecological systems, which appears in the form of discrete individuals in the population, we should use in models of population dynamics a paradigm that speaks of the variability of these individuals and the discontinuity of basic demographic processes in populations. This should result in the further development of individual-based modelling in ecology as well as the development of experimental individual-based ecology. The paradigm of dependence on density in a slightly altered form and the assumption of the continuity of ecological processes can continue to be used in those branches of ecology that deal with the cycling of matter and the flow of energy through ecological systems.